Experimental study of tsunami bore induced forces on vertical seawall - Mokhtar, Zaty Aktar; Yusuf, Badronnisa; Mohammad Ali, Thamer Ahmad; Hamzah, Saiful Bahri (Universiti Putra Malaysia Press, 2019)
Field surveys of the 2011 Tohoku Tsunami reported massive failures of many seawalls and coastal barriers. The massive damages are vivid evidence that there are flaws in the design of seawalls and barriers. With this as the background, a sequence of laboratory experiments using dam-break waves was performed to simulate the interactions between the tsunami-like bore flow and vertical seawall as well as to measure the bore-induced pressures and to estimate forces exerted on the vertical seawall model. The experimental result revealed that the maximum pressure (approximately 8 kPa) exerted on the vertical seawall was measured at the lowest pressure sensor location. Experimental data were used to re-examine the relevant empirical formulae found in the literature. The obtained results could be useful for calibrating mathematical and numerical models as well as for future research concerning the design of tsunami barriers.